SIMULTANEOUS CONTENT ANALYSIS OF RIFAMPICIN, ISONIAZID, AND PYRAZINAMIDE IN TABLET DOSAGE FORM BY SPECTROPHOTOMETRY ULTRAVIOLET WITH DWM AND RSM - Luthvia Luthvia; Muhammad Andry (Universitas Muhammadiyah Magelang, 2022)
Treatment of active tuberculosis requires the use of combinations of drugs. One of the common combination of drugs to serve as anti-tubercular medication is rifampin, isoniazid and pyrazinamide. However, a research conducted by the Food Drug Administration (FDA) concluded that the combination of anti-tubercular medication may pose some patients to the risk of sub-optimal drug exposure, which may lead to less optimal treatment. This study aimed to determine the drug level of combination of anti-tubercular medication, namely rifampin, isomiazid, and pyrazinamide and to develop a spectrophotometric method using the dual wavelength method (DWM) and ratio substaction method (RSM) in tablet preparations on the market without separation. During the preparation, methanol was used as the solvent, followed by dilution, determination of calibration curve, determination of wavelength (λ), measurement, data analysis and validity test with several parameters ranging from linearity, accuracy, precision, LOD, and LOQ. The research revealed that the drug levels of rifampin, isoniazid, and pyrazinamide from the ultraviolet spectrophotometric method using sequential DWM were 100.3±1.8785; 99.98±2.5943; 100.03±2.076 and the results of the ultraviolet spectrophotometric method using RSM sequentially were 99.73±0.5437; 99.84±1.7598; 99.91±1.4762. Both methods succeeded in determining the drug level of the combination of rifampin, isoniazid, and pyrazinamide in tablet preparations without separation and the results of the validation parameters met the requirements.